Automated Validation Of Software Product Lines Using First Order Logic Rules - Abdelrahman Elfaki, Abdelrahman Osman (2010)
This research aims to accentuate the extraction of high quality software products from SPL. Usually, a medium-sized SPL contains thousands of features with constraint dependency rules between them. Therefore, the validation of SPL is a vital process and it is not feasible to be done manually.